Pengaruh Sanksi dari Tindakan Indisipliner terhadap Kinerja Karyawan pada Divisi Collection PT. Summit Oto Finance Pekanbaru - Andry Andry (Universitas Samudra, 2019)
The study was conducted at the collection division of PT. Summit Oto Finance Pekanbaru with the aim of research to determine the effect of sanctions from disciplinary actions on employee performance. The number of samples used was 42 people, using the census method. The analysis used is validity test, reliability test, classic assumption test, F test and T test. The results of the analysis using SPSS can be seen that the position reduction variable has a negative effect on performance, transfer of position and termination has a positive effect on employee performance while complaints to parties authority does not affect employee performance. The results of the analysis using the coefficient of determination, the results are 82.2% and the remaining 17.8% are not examined